A Study of the Usage of Biofeedback Techniques to Improve Self Performance and HRV Profile Among Ikhtiar Malaysia Entrepreneurs - Nazrolnizah, Mohamad Noorzeli; Muhammad Nubli, Abdul Wahab (Secholian Publication PLT, 2016)
Self performance is important among entrepreneurs due to increasing the business enhancement. Nevertheless, previous literature showed that there are less current study which focused on the self performance using Biofeedback techniques among entrepreneurs in Malaysia. Thus, this study was aimed; 1) to look at how Emwave Biofeedback techniques can be used to improve self performance among Ikhtiar Malaysia women entrepreneurs and 2) to improve the HRV score among participants through increased the HF coherence. A total of 10 respondents were recruited in this study. The changing nature of Heart Rate variability (HRV) of HF, LF and VLF frequencies was measured through Biofeedback Emwave training techniques. The HRV Biofeedback techniques were used to determine the emotional state and the balance ability between individual Sympathetic and Parasympathetic systems. This balance is important to enable women entrepreneurs to control internal and external stimuli to be adapted to their business environment. The study showed that the technique is able to improve the characteristics of HRV to increase self performance among women entrepreneurs. The study found that respondents who successfully completed the HRV training able to increase their self performance in term of HRV score and businesses. Result showed that there was a positive correlation (0.80-1.00) between all the business and HRV. This showed that Emwave Biofeedback training is appropriate to be used as an intervention program to improve self performance and business enhancement among the participants. Thus, this study concludes that HRV Biofeedback techniques can be an important measure in gauging business entrepreneur’s health and performance.